2017
DOI: 10.1017/s0033291717003129
|View full text |Cite
|
Sign up to set email alerts
|

Stepped care in primary care – guided self-help and face-to-face cognitive behavioural therapy for common mental disorders: a randomized controlled trial

Abstract: Stepped care can be effective and resource-efficient to treat CMD in primary care, leading to high remission rates with limited therapist resources. Face-to-face CBT speeded up recovery compared with continued GSH. At follow-ups after 6 and 12 months, remission rates were similar in the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 156 publications
1
22
0
Order By: Relevance
“…The ICBT protocol was a 12-week treatment based on a CBT protocol for AD and ED that was developed in clinical practice and evaluated in 2 randomized clinical trials conducted by our research group [22,23]. A key assumption of the treatment was that stress is a natural and necessary part of life, but that negative health consequences result, in part, from maladaptive behaviors adopted in response to stressors.…”
Section: Interventionsmentioning
confidence: 99%
“…The ICBT protocol was a 12-week treatment based on a CBT protocol for AD and ED that was developed in clinical practice and evaluated in 2 randomized clinical trials conducted by our research group [22,23]. A key assumption of the treatment was that stress is a natural and necessary part of life, but that negative health consequences result, in part, from maladaptive behaviors adopted in response to stressors.…”
Section: Interventionsmentioning
confidence: 99%
“…As no evidence‐based treatments exist for AD and ED, these disorders were treated with a CBT protocol that has been developed by our research group and tested in clinical practice since 2007. The treatment has been included in three randomized trials as face‐to‐face treatment (present study: Salomonsson et al ., ), stepped care with guided self‐help and face‐to‐face treatment (Salomonsson et al ., ), and as an Internet‐based treatment (Lindsäter et al ., ). The treatment is based on a model assuming that these disorders are maintained by a deficit of recuperation (Geurts & Sonnentag, ; Lisspers, Almén, & Sundin, ) that can be caused by for example difficulties to relax, extensive rumination, or aversive consequences of relaxing (e.g., a person may feel shame or guilt if taking a rest instead of working or helping friends or family).…”
Section: Methodsmentioning
confidence: 99%
“…The efficacy of iCBT for depression in primary care so far has been investigated by only one study, wherein iCBT has been shown to be more effective than treatment-as-usual (Proudfoot et al, 2004). Salomonsson et al (2017) have argued that using a stepped-care model 2 is an effective and efficient way to achieve improvements for nearly two thirds of primary care patients with common mental disorders while using fewer therapist resources.…”
Section: Final)mentioning
confidence: 99%
“…A literature review of randomized controlled trials of iCBT in primary care in Europe, the USA and Australia proved that additional professional support is required to engage depressed patients with self-help internet-based psychotherapies. At present, computerized CBT is offered by many healthcare systems as a minimally supported low-intensity psychological intervention and as part of a stepped-care framework (Salomonsson et al, 2017;Høifødt et al, 2013). The level of support for each patient is different and it varies mainly in severity of depression and the patient's ability to perform tasks online.…”
Section: The Global Experience Of Icbt In Primary Carementioning
confidence: 99%
See 1 more Smart Citation